STRATEGI PEMASARAN BERAS DAN DAMPAK SOSIAL EKONOMI TERHADAP PEDAGANG PENGEPUL DI DESA BENTE KECAMATAN KABAWO KABUPATEN MUNA - Andi Samsudin Haerun; La Nalefo; La Ode Kasno Arif (Jurnal Ilmiah Inovasi dan Komunikasi Pembangunan Pertanian, 2023)
The objective of this study is to analyze the marketing strategy of rice and its impact on the socio-economic status of collecting traders in Bente Village, Kabawo District, Muna Regency. The population of the study consisted of 9 members of the Bangkit Jaya Farmer Group, who are rice producers, and the sample was selected using the census sampling technique. Data were collected through observation, interviews, and documentation using media or interview guide instruments. The study employed a descriptive qualitative analysis method, which involved three stages: data reduction, data presentation, and conclusion drawing. The findings revealed that the Bangkit Jaya Farmer Group's sales partner strategy for rice involves price cuts and no delivery fees. The brand strategy focuses on rice with special characteristics, using local rice as raw material. The applied price strategy involves reducing the price of rice sales with partners for every purchase of approximately 1 ton. Rice marketing has a significant impact on the socioeconomic conditions of members of the Bangkit Jaya Farmer Group and their families, including education, health, income, and asset ownership.